Airway macrophages display decreased expression of receptors mediating and regulating scavenging in early cystic fibrosis lung disease - Slimmen, Lisa J. M.; Giacalone, Vincent D.; Schofield, Craig; Horati, Hamed; Manaï, Badies H. A. N.; Estevão, Silvia C.; Garratt, Luke W.; Peng, Limin; Tirouvanziam, Rabindra; Janssens, Hettie M.; Unger, Wendy W. J. (Frontiers in Immunology, 2023)
Background: Cystic fibrosis (CF) airway disease is characterized by chronic inflammation, featuring neutrophil influx to the lumen. Airway macrophages (AMs) can promote both inflammation and resolution, and are thus critical to maintaining and restoring homeostasis. CF AM functions, specifically scavenging activity and resolution of inflammation, have been shown to be impaired, yet underlying processes remain unknown. We hypothesized that impaired CF AM function results from an altered expression of receptors that mediate or regulate scavenging, and set out to investigate changes in expression of these markers during the early stages of CF lung disease. Methods: Bronchoalveolar lavage fluid (BALF) was collected from 50 children with CF aged 1, 3 or 5 years. BALF cells were analyzed using flow cytometry. Expression levels of surface markers on AMs were expressed as median fluorescence intensities (MFI) or percentage of AMs positive for these markers. The effect of age and neutrophilic inflammation, among other variables, on marker expression was assessed with a multivariate linear regression model. Results: AM expression of scavenger receptor CD163 decreased with age (p = 0.016) and was negatively correlated with BALF %neutrophils (r = -0.34, p = 0.016). AM expression of immune checkpoint molecule SIRPα also decreased with age (p = 0.0006), but did not correlate with BALF %neutrophils. Percentage of AMs expressing lipid scavenger CD36 was low overall (mean 20.1%±16.5) and did not correlate with other factors. Conversely, expression of immune checkpoint PD-1 was observed on the majority of AMs (mean PD-1pos72.9%±11.8), but it, too, was not affected by age or BALF %neutrophils. Compared to matched blood monocytes, AMs had a higher expression of CD16, CD91, and PD-1, and a lower expression of CD163, SIRPα and CD36. Conclusion: In BALF of preschool children with CF, higher age and/or increased neutrophilic inflammation coincided with decreased expression of scavenger receptors on AMs. Expression of scavenging receptors and regulators showed a distinctly different pattern in AMs compared to blood monocytes. These findings suggest AM capacity to counter inflammation and promote homeostasis reduces during initiation of CF airway disease and highlight new avenues of investigation into impaired CF AM function.